Investigation of combinations of rationally selected bioengineered nisin derivatives for their ability to inhibit Listeria in broth and model food systems. (October 2021) - Nyhan, Laura; Field, Des; Hill, Colin; Callanan, Michael; Begley, Máire
Abstract: In this study, we examined the ability of nisin A and a rationally assembled bank of 36 nisin derivative producing Lactococcus lactis strains to inhibit Listeria. A broth-based bioluminescence assay for screening single and combinations of bioengineered nisin derivatives using cell-free supernatants (CFS) from nisin derivative producing strains was developed. In this way, we screened 630 combinations of nisin derivative producing strains, identifying two (CFS from M17Q + N20P and M17Q + S29E) which exhibited enhanced anti-listerial activity when used together compared to when used alone, or to the nisin A producing strain. Minimal inhibitory concentration assays performed with purified peptides revealed than when used singly, the specific activities of M17Q, N20P and S29E (3.75–7.5 μM) against L. innocua were equal to, or less than that of nisin A (MIC of 3.75 μM). Broth-based growth curve assays using purified peptides demonstrated that use of the double peptide combinations and a triple peptide combination (M17Q + N20P + S29E) resulted in an extended lag phase of L. innocua, while kill curve assays confirmed the enhanced bactericidal activity of the combinations in comparison to the single derivative peptides or nisin A. Furthermore, the enhanced activity of the M17Q + N20P combination was maintained in a model food system (frankfurter homogenate) at both chill (4 °C) and abusive (20 °C) temperature conditions, with final cell numbers significantly less (1–2 log10 CFU/ml) than those observed with the derivative peptides alone, or nisin A. To our knowledge, this study is the first investigation that combines bioengineered bacteriocins with the aim of discovering a combination with enhanced antimicrobial activity. Highlights: Anti-listerial effect of supernatants from bioengineered nisin derivatives was examined. A broth-based bioluminescence assay was developed to examine antimicrobial activity. M17Q + N20P and M17Q + S29E were enhanced against Listeria in broth. The enhanced activity of M17Q + N20P was maintained in frankfurter homogenate.